2020
DOI: 10.3389/fpsyg.2020.02119
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Strategy Use During the Performance of Hippocampal-Dependent Tasks

Abstract: Recalling the past, thinking about the future, and navigating in the world are linked with a brain structure called the hippocampus. Precisely, how the hippocampus enables these critical cognitive functions is still debated. The strategies people use to perform tasks associated with these functions have been under-studied, and yet, such information could augment our understanding of the associated cognitive processes and neural substrates. Here, we devised and deployed an in-depth protocol to examine the expli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 61 publications
(106 reference statements)
0
14
0
Order By: Relevance
“…(2019) recently reported that the ability to construct scene imagery explained the relationships between episodic memory, imagining the future and spatial navigation task performance. The prominence of scenes was further emphasised in another study involving the same sample, where the explicit strategies people used to perform episodic memory recall, future thinking and spatial navigation tasks was assessed ( Clark, Monk, & Maguire, 2020 ). In each case, the use of scene visual imagery strategies was significantly higher than for all other types of strategies (see also Andrews-Hanna, Reidler, Sepulcre, Poulin, & Buckner, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2019) recently reported that the ability to construct scene imagery explained the relationships between episodic memory, imagining the future and spatial navigation task performance. The prominence of scenes was further emphasised in another study involving the same sample, where the explicit strategies people used to perform episodic memory recall, future thinking and spatial navigation tasks was assessed ( Clark, Monk, & Maguire, 2020 ). In each case, the use of scene visual imagery strategies was significantly higher than for all other types of strategies (see also Andrews-Hanna, Reidler, Sepulcre, Poulin, & Buckner, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, a recent individual differences study involving a large sample of participants ( n = 217), found that the ability to construct scene imagery fully mediated the relationships between autobiographical memory recall and other hippocampal‐dependent functions such as future thinking and spatial navigation (Clark et al, 2019). Moreover, in the same sample, strategies involving scene imagery predominated when recollecting autobiographical memories (Clark, Monk, & Maguire, 2020). It is also notable that the volume of the pre/parasubiculum is of particular clinical importance as a diagnostic marker.…”
Section: Discussionmentioning
confidence: 99%
“…Scene imagery features prominently when we recall autobiographical memories, imagine the future and navigate around in the world ( Clark et al, 2020 ). Consequently, in this study we sought to better understand how scene representations are supported by the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The vmPFC has strong anatomical and functional connections with the hippocampus and lateral temporal cortex ( Andrews-Hanna et al, 2010 ; Catani et al, 2012 ). Together, these structures are often co-activated during fMRI studies involving scene processing ( Zeidman et al, 2015 ; McCormick et al, 2021 ), and tasks that are known to involve scene imagery ( Clark et al, 2020 ) such as autobiographical memory recall, future thinking and spatial navigation ( Svoboda et al, 2006 ; Spreng et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%